PENGARUH EKSTRAK BUAH PEDADA PUTIH (Sonneratia alba) TERHADAP MOTILITAS SPERMATOZOA MENCIT (Mus musculus) JANTAN GALUR DDY - Laksmiwati Nabila (2023)
Male participation in the family planning program in Indonesia is still low compared to another countries. This is due to permanent non hormonal contraception like vasectomy. Therefore, it is important to investigate alternative strategies for contraceptions that are safe and effective. Pedada fruit (Sonneratia alba) is now being studied for their potencies as contraception alternatives. The aim of our study was to explore the effect of Pedada Fruit (Sonneratia alba) on spermatozoa motility. This experimental study is conducted at iRATco Veterinary Laboratory Services Bogor. The research was conducted in May-July 2023. The subjects used were male mice (Mus musculus) DDY strain. Inclusion criteria for the study sample included healthy and active male mice, aged 8-12 weeks, weighing ± 20-40 grams. Mice with anatomical abnormalities and those that had been used for previous experiments were excluded. Mice that met the restriction criteria were then divided into five groups: Mice that met the restriction criteria were then divided into five groups: negative control (0.9% NaCl), positive control (1% NaCMC), and treatment 1 (200mg/KgBB), treatment 2 (300mg/KgBB), and treatment 3 (400 mg/KgBB). Bivariate analysis using Kruskal-Wallis and Post-Hoc obtained results of p <0.05 between the negative control with treatment 2 and treatment 3 which indicated that there was a significant difference between the negative control with treatment 2 (p=0.038) and treatment 3 (p=0.038). Mangrove fruit (Sonneratia alba) extract with concentrations of 300 mg/kg (treatment 2) and 400 mg/kg (treatment 3) showed significant effect on spermatozoa motility of the mice.